The Mbeya Antimicrobial Stewardship Team: Implementing Antimicrobial Stewardship at a Zonal-Level Hospital in Southern Tanzania - Hall, Jeffrey W. (Pharmacy (Basel), 2020)
Background: In 2017, Mbeya Zonal Referral Hospital (MZRH) and the University of South Carolina (UofSC) agreed to collaboratively strengthen antimicrobial prescribing in the southern highlands of Tanzania and train a new generation of clinicians in responsible antimicrobial use. Methods: Key stakeholders and participants were identified and the Mbeya Antimicrobial Stewardship Team (MAST) was created. The team identified assets brought by the collaborators, and four investigations of baseline needs were developed. These investigations included (a) a baseline clinician survey regarding antimicrobial resistance and stewardship, (b) a serial chart review of inpatient antimicrobial prescribing practices, (c) an investigation of antimicrobial resistance rates using existing isolates at the MZRH laboratory, and (d) a survey of antimicrobial availability at community pharmacies in the city. Results: 91% of physicians believe antimicrobial resistance is problem in Tanzania, although only 29% of physicians were familiar with the term “antimicrobial stewardship”. Escherichia coli isolates had resistance rates of over 60% to the commonly used agents ciprofloxacin, trimethoprim-sulfamethoxazole, and ceftriaxone. Thirteen out of 14 community pharmacies offered over-the-counter antibiotics for upper respiratory symptoms. Conclusions: International antimicrobial stewardship collaborations can successfully identify opportunities and needs. Evaluating the team’s efforts to improve patient outcomes will be essential.